1997
DOI: 10.1007/bf01983671
|View full text |Cite
|
Sign up to set email alerts
|

Low/high temperature relationships in dinitramide salts by DEA/DSC and study of oxidation of aluminum powders by DSC/TG

Abstract: The dinitramide salts of ammonia (ADN), hexamethylenetetramine (HDN), potassium (KDN), and sodium (NaDN) showed a linear relationship between the DSC rate of decomposition at the peak maximum and the DEA tan5 value at the low temperature transition peak. As the cation basicity increased in the series ADN < HDN < KDN Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A less pronounced decrease in E a with increasing reaction extent at a high flow rate of the carrier gas was believed to be evidence for the catalytic action of NO 2 [36]. A DSC investigation by Tompa et al [39] showed that ADN decomposition in a sealed pan had a lower E a than that in an unsealed pan with a pin-hole. A lower value (E a = 29.5 kcal/mole) was observed under pressurized conditions (air or He) than at one atmosphere (N 2 or He).…”
Section: Thermal Decomposition Kineticsmentioning
confidence: 96%
See 2 more Smart Citations
“…A less pronounced decrease in E a with increasing reaction extent at a high flow rate of the carrier gas was believed to be evidence for the catalytic action of NO 2 [36]. A DSC investigation by Tompa et al [39] showed that ADN decomposition in a sealed pan had a lower E a than that in an unsealed pan with a pin-hole. A lower value (E a = 29.5 kcal/mole) was observed under pressurized conditions (air or He) than at one atmosphere (N 2 or He).…”
Section: Thermal Decomposition Kineticsmentioning
confidence: 96%
“…In comparison with KDN, sodium dinitramide (NaDN), and hexamethylenetetramine dinitramide (HMDN), ADN has the lowest decomposition temperature and the highest decomposition rate and heat release [39]. ADN is less stable thermally than KDN, but much more stable than NH 4 NO 2 and alkyl dinitramide (alkyl-N(NO 2 ) 2 ) [2].…”
Section: Overall Thermal Decomposition Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…18,19 The oxidation of aluminum is limited by the diffusion of species through the protective alumina film, and different steps are observed when the diffusion resistance of the film changes as a result of polymorphic transformations in alumina. A similar scenario is expected for the oxidation of Al-Ti mechanical alloys, however, the sequence of the polymorphic phase changes could be altered.…”
Section: Oxidationmentioning
confidence: 99%
“…This sequence of aluminum oxidation was observed in several earlier studies. 18,19 Recently, a mechanism has been proposed connecting the stepwise oxidation of aluminum with polymorphic phase changes occurring in the growing layer of Al 2 O 3 . 20 Oxidation of titanium powder produces a broad exothermic event starting at about 600°C and continuing until about 1050°C.…”
Section: Oxidationmentioning
confidence: 99%